TEAMMATES CONSULT STRATEGY TOWARDS STUDENTS’ MOTIVATION AND READING NARRATIVE TEXT - Fathurrahman Imran; K. Dedy Sandiarsa S. (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2018)
This research was generally attempted to find the effect of Teammates Consult Strategy towards students’ motivation and reading narrative text at FPBS IKIP Mataram. This research was an experimental research with MANOVA as the data analysis. The population of this research was the students of the third semester of FPBS students. The sample of the research was 45 students consisted of two classes. From the research data found that with the mean score of motivation was 81,04 and control group was 78,00. With the significance 0.000 < 0,05. While the mean for the reading of experimental group was 82,54 and control group was 79,09 with the significance 0.000 < 0,05. It can be concluded that the result of the research showed that there was a significant effect of Teammates Consult strategy towards students’ motivation, there was a significant effect of Teammates consult strategy toward reading narrative text, there was a significant effect of motivation and reading narrative text, there was a significant effect of Teammates Consult strategy towards students motivation and reading narrative text and there was no correlation between motivation and reading narrative text.